Residents’ perception of urban forestry impact on biodiversity conservation in Ibadan metropolis, Nigeria (2013)
Population growth and unregulated settlement pattern impede biodiversity conservation especially in urban areas. This paper investigated the perception of urban residents in Ibadan metropolis, Nigeria on improving the environment through urban greening and renewal. Respondents were drawn from residents of two educational institutions (University of Ibadan and The Polytechnic, Ibadan) and their respective adjoining communities (Agbowo and Apete). Relevant information was obtained from them using a set of questionnaire. Data obtained were analysed using descriptive statistical tools. Results show that level of understanding of the importance of trees was high in University of Ibadan (93.4%) followed by its adjoining community (Agbowo: 63.3%) and lowest in The Polytechnic (8.2%). Respondents expressed desire for tree planting especially around their residence when under progressively longer duration of residency. All the residents have preference for planting fruit trees except in University of Ibadan where preference was highest for planting other economic tree species. The fear of wildlife usually associate with vegetation cover and possible fire outbreak were top constraints expressed by respondents which could limit their active participation in urban forestry programmes. Subsidized and affordable tenancy through public-private partnership, restrictions in slum growth and mandatory fire tracing in residential and business premises were advocated measures for improving urban renewal programmes.